KELOMPOK TANI SEBAGAI MEDIA INTERAKSI SOSIAL (KAJIAN ANALISIS FUNGSIONAL STRUKTURAL TALCOTT PARSON) - Eny Lestari (AGRITEXTS: Journal of Agricultural Extension, 2004)
Farmer group or social interaction media is very efective to give innovation, and the smallest unit from non formal institution from rural community. Social interaction always happen in social live, expecially in rural community group, who stil have strong family relationship. Farmer motivation by became a member of farmer group are very various. farmer group or social interaction  media have advantage.for.farmer as: 1. Adaptation of the environmental 2. To reac ther purpose 3. In tegration tools 4. A way to keep culture value, norm, cooperation in rural live